Desenvolvimento de formulações para uso tópico contendo extrato seco de pau d'arco (Handroanthus impetiginosus) - Pereira, Pedro Igor de Oliveira (2023)
Handroanthus impetiginosus is a plant species that has lapachol as one of the main metabolites present in its inner bark. Lapachol is a molecule with well-described antineoplastic and anti-inflammatory activity, having already been published in pharmaceutical forms for topical use. However, the herbal complex present in the plant species had not yet been explored in the production of these formulations. The aim of this work was to develop formulations for topical use containing the dry extract of H. impetiginosus (HIDE). HIDE was produced from 20% tincture of H. impetiginosus (HIT) containing a lapachol content of 15.59%, a much higher concentration than HIT (0.14%), as expected. HIT was characterized by pH, dry residue and lapachol content, and HIDE was characterized by loss on desiccation and lapachol content. The biological activities of lapachol were predicted by in silico models. The antioxidant activity of HIDE was confirmed by the content of phenolic compounds and by the DPPH radical scavenging assay. The formulations were characterized regarding their macroscopic and microscopic characteristics, centrifugation, pH, density, spreadability and rheological behavior. Thirty-seven biological activities were identified in the in silico prediction methods, with Pa > 0.3, especially the “antioxidant” (0.648) and “free radical scavenger” (Pa = 0.564) activity. The effectiveness of the total phenolic compounds content showed a value equal to 257.11 ± 3.8 mgEAG/g of extract, indicating significant antioxidant activity, confirmed by the DPPH assay (inhibition of 93.74 ± 0.6%; IC50 = 10.17 ± 0.51 μg/mL). The formulations produced from hide (gel – HIG; emulgel – HIEG) showed an intense red color, as observed in previous studies, denoting an alkaline pH, the medium in which lapachol becomes more soluble. HIG and HIEG demonstrated stability in the period of 30 days in relation to the evaluated parameters, except in the rheological behavior evaluation, where a significant increase in capacity was found after 30 days (p < 0.05). HIG and HIEG showed pseudoplastic behavior and a release profile that best fit Higuchi's kinetic model, which follows Fick's Law. HIEG released more lapachol after 24h (HIG – 13,34%; HIEG – 30,55%). Therefore, it is possible to conclude that the methodology used extracted lapachol, adding it to the HIDE composition, with a phytocomplex that demonstrated expressive antioxidant activity. HIDE could also be used in formulations for topical use, where lapachol crystals are dissolved, with the emulgel presenting the best active release profile. The need for further studies evaluating the biological activities of HIDE and its skin penetration is highlighted.